Ni3s2 quantum wire loaded monatomic material, and preparation method and application thereof

CN117604565BActive Publication Date: 2026-11-03GUANGDONG UNIV OF PETROCHEMICAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311595308.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2026-11-03
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

Existing methods for preparing Ni3S2 nanomaterials are complex and cannot simultaneously achieve good catalytic activity and stability, thus limiting their application in hydrogen production through water electrolysis.

Method used

Using thiourea and ferrocene as raw materials, Ni3S2 quantum wire-loaded single-atom materials were prepared on a nickel foam substrate through gas flow reaction at a specific temperature. A carbon coating layer was formed and doped with N atoms and loaded with iron atoms to optimize the electrocatalytic performance.

Benefits of technology

It reduces overpotential and Tafel slope, improves electrochemical active area and stability, exhibits good redox catalytic activity and stability, and has a simple preparation method with readily available raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117604565B_ABST
    Figure CN117604565B_ABST
Patent Text Reader

Abstract

The application relates to a Ni3S2 quantum wire loaded monatomic material and a preparation method and application thereof. The preparation method of the Ni3S2 quantum wire loaded monatomic material comprises the following steps: placing thiourea and ferrocene in the upstream of airflow, placing foamed nickel in the downstream of airflow, and reacting at 400-500 DEG C for 1-1.5 hours, so that the Ni3S2 quantum wire loaded monatomic material is obtained. On the basis of thiourea as a raw material, ferrocene is further introduced, so that the obtained Ni3S2 quantum wire loaded monatomic material has a lower overpotential, a lower Tafel slope, a significantly increased double-layer capacitance, a large electrochemical active area, and good stability of an OER catalyst. In addition, the preparation method only needs one-step heating to prepare the Ni3S2 quantum wire loaded monatomic material, and the process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of single-atom catalyst technology, and more specifically, to a Ni3S2 quantum wire-supported single-atom material, its preparation method, and its application. Background Technology

[0002] The fossil fuel crisis and rapid economic development necessitate the development of economical, efficient, and environmentally friendly energy storage and conversion systems. Hydrogen energy, due to its high energy density and pollution-free characteristics, is considered a promising alternative to fossil fuels, possessing broad application prospects while also facing various problems and challenges. Water electrolysis for hydrogen production is a highly promising technology, but its efficiency is primarily limited by the high reaction barriers and slow kinetics of the water splitting process (OER).

[0003] In water electrolysis for hydrogen production, the OER (Oxygen Evolution Electrode) is a slow four-electron transfer process with a high overpotential, limiting its effectiveness. Noble metals can reduce the overpotential of the OER, but their high cost and limited availability restrict their widespread application. Transition metal sulfides, on the other hand, are inexpensive, abundant, and possess unique physical and chemical properties, offering broader application prospects compared to noble metals. Transition metal sulfide-based materials have a high specific surface area, facilitating the exposure of numerous active sites, and exhibit high conductivity and stability. The activity of some transition metal sulfides is already very close to that of noble metal catalysts. To date, various metal sulfides (Ni3S2, MoS2, FeS2, etc.) have been extensively studied in the OER field, with nickel sulfides attracting particular attention due to their unique d-electron configuration, good conductivity, and environmental friendliness. In the water electrolysis reaction, the OER involves a slow four-electron-proton coupling reaction, which is more complex than the simple two-electron transfer in the HER (Hydrogen Evolution) reaction. Therefore, improving the efficiency of water electrolysis largely depends on the performance of the OER catalyst. Ni3S2 has low room temperature conductivity, is abundant in nature, is environmentally friendly, and is simple to prepare. However, during charge-discharge processes, the discharge product lithium sulfide dissolves in ordinary electrolytes. To overcome this problem, it is necessary to prepare nanoscale Ni3S2. Nanostructured Ni3S2 can enhance conductivity, improve electrode velocity, and increase electrochemical performance. For example, a Chinese patent entitled "A Preparation Method and Application of Fe-Doped Ni3S2 Electrode Material" provides a nanostructured Ni3S2 material.

[0004] However, current methods for preparing Ni3S2 nanomaterials are quite complex, resulting in high production costs. Furthermore, good catalytic stability could broaden the application of Ni3S2 nanomaterials in hydrogen production, but the catalytic stability of current Ni3S2 nanomaterials still needs to be improved. Summary of the Invention

[0005] The primary objective of this invention is to overcome the problems that existing methods for preparing Ni3S2 nanomaterials are complex and cannot simultaneously achieve good catalytic activity and catalytic stability, and to provide a method for preparing Ni3S2 quantum wire-supported single-atom materials.

[0006] A further objective of this invention is to provide a Ni3S2 quantum wire-supported single-atom material.

[0007] A further objective of this invention is to provide the application of the above-mentioned Ni3S2 quantum wire-supported single-atom material as a catalyst in water electrolysis for hydrogen production.

[0008] The above-mentioned objective of the present invention is achieved through the following technical solution:

[0009] A method for preparing Ni3S2 quantum wire-supported single-atom material includes the following steps:

[0010] Thiourea and ferrocene are placed upstream of the gas flow, and nickel foam is placed downstream of the gas flow. The reaction is carried out at 400-500℃ for 1-1.5 hours to obtain the Ni3S2 quantum wire-supported single-atom material.

[0011] Studies have found that the types of raw materials introduced during the preparation of nano-Ni3S2 materials have a significant impact on the formation of nanomaterials. These impacts include whether a reaction can occur, whether nanomaterials can be successfully prepared, the microstructure of the prepared nanomaterials, and the catalytic performance of the prepared nanomaterials, among others.

[0012] The inventors of this invention discovered that by using thiourea as a raw material and nickel foam as a supporting substrate, and conducting a reaction at a specific temperature for a certain period of time, Ni3S2 can be grown in situ on nickel foam to obtain Ni3S2 nanomaterials. Compared with untreated nickel foam, this Ni3S2 nanomaterial, as an OER catalyst, exhibits a reduced overpotential and a reduced Tafel slope, but the double-layer capacitance does not change significantly. In the OER catalyst stability test, the current density decreases significantly over time (e.g., within 12 hours), indicating poor stability.

[0013] The inventors of this invention further discovered that by using thiourea and ferrocene as raw materials and nickel foam as a supporting substrate, and conducting a reaction at a specific temperature for a certain period of time, Ni3S2 quantum wire-supported single-atom materials can be prepared. Specifically, by further introducing ferrocene into thiourea as a raw material, Ni3S2 can be grown in situ on nickel foam, and the surface of the grown Ni3S2 is coated with a carbon layer, which is doped with N atoms and loaded with iron atoms. This can reduce the mass of nickel foam while shortening the electron transport distance, thereby optimizing the electrocatalytic performance. Furthermore, the Ni3S2 quantum wires have a self-bent structure, increasing the specific surface area and enabling rapid electron transport, effectively improving the actual specific capacity of the material. These two effects result in a further reduction in overpotential and Tafel slope when the obtained Ni3S2 quantum wire-supported single-atom material is used as an OER catalyst, with a significantly increased double-layer capacitance and a larger electrochemical active area. At the same time, the current density in the OER catalyst stability test does not decrease significantly over time (e.g., within 12 hours), and even shows a certain degree of increase, exhibiting good OER catalytic activity and stability.

[0014] Furthermore, this preparation method requires only one heating step to prepare Ni3S2 quantum wire-loaded single-atom materials. The process is simple, the raw materials are readily available, and it can be mass-produced.

[0015] Preferably, the mass ratio of thiourea to ferrocene is 1:(0.8-1.5).

[0016] Preferably, the airflow is an inert gas flow.

[0017] More preferably, the inert gas flow is an argon flow.

[0018] Preferably, the airflow velocity is 40 to 60 sccm.

[0019] Preferably, the mass-to-volume ratio of thiourea to nickel foam is 1 mg:(0.03–0.08) cm³. 3 .

[0020] Preferably, before placing the nickel foam downstream of the airflow, the process further includes a step of cleaning and drying the nickel foam.

[0021] Specifically, the cleaning steps are as follows: the nickel foam is cleaned sequentially with acetone, ethanol and deionized water.

[0022] Preferably, the reaction is carried out in a tube furnace.

[0023] Specifically, thiourea (CH4N2S) and ferrocene [Fe(C5H5)2] are loaded into a ceramic boat, and dried nickel foam is placed in another ceramic boat. These two ceramic boats are then placed in a tube furnace, with the boat containing thiourea and ferrocene near the furnace inlet and the boat containing nickel foam near the furnace outlet. The gas flow direction is from the furnace inlet to the outlet, with thiourea upstream and ferrocene downstream of the gas flow in the boat containing thiourea and ferrocene. An inert gas flow is introduced into the tube furnace at a velocity of 40–60 sccm, and the furnace is heated to 400–500°C and maintained for 1–1.5 hours to obtain the Ni3S2 quantum wire-loaded single-atom material.

[0024] A Ni3S2 quantum wire-loaded single-atom material was prepared by the above-described preparation method.

[0025] The application of the aforementioned Ni3S2 quantum wire-supported single-atom material as a catalyst in water electrolysis for hydrogen production is also within the scope of protection of this invention.

[0026] Preferably, the catalyst is used to catalyze the electrochemical oxygen evolution reaction.

[0027] Compared with the prior art, the beneficial effects of the present invention are:

[0028] This invention further introduces ferrocene into thiourea, resulting in Ni3S2 quantum wire-supported single-atom materials that exhibit low overpotential, low Tafel slope, large double-layer capacitance, and large electrochemical active area when used as OER catalysts. Furthermore, the current density in OER catalytic stability tests does not significantly decrease over time (e.g., within 12 hours), and even shows a certain degree of increase, demonstrating excellent OER catalytic activity and stability. In addition, this preparation method requires only one heating step to prepare Ni3S2 quantum wire-supported single-atom materials, making the process simple, the raw materials readily available, and suitable for mass production. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the preparation process of Ni3S2 quantum wire-loaded single-atom material in Example 1.

[0030] Figure 2 A to C are SEM images of the Ni3S2 quantum wire-loaded single-atom material in Example 1 at different magnifications; Figure 2 D to E are TEM images of the Ni3S2 quantum wire-loaded single-atom material in Example 1 at different magnifications; Figure 2 F is the result of energy-dispersive X-ray spectroscopy analysis of the Ni3S2 quantum wire-loaded single-atom material in Example 1.

[0031] Figure 3 This is a high-resolution TEM image of the Ni3S2 quantum wire-loaded single-atom material from Example 1.

[0032] Figure 4 The image shows the XRD pattern of the Ni3S2 quantum wire-supported single-atom material in Example 1.

[0033] Figure 5 This is a high-resolution XPS spectral image of the Ni3S2 quantum wire-loaded single-atom material of Example 1.

[0034] Figure 6 A is the OER polarization curve of each sample in the performance test; Figure 6 B is the Tafel slope diagram for each sample in the performance test.

[0035] Figure 7 The image shows the CV curves of each sample in the performance test at different scan rates.

[0036] Figure 8 A shows the double-layer capacitance (Cdl) of each sample in the performance test. Figure 8 B represents the Nyquist plots of each sample under different overpotentials during performance testing.

[0037] Figure 9 This is a graph showing the OER time measurement for each sample in the performance test. Detailed Implementation

[0038] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.

[0039] Example 1

[0040] This embodiment provides a method for preparing Ni3S2 quantum wire-supported single-atom materials, including the following steps:

[0041] First, nickel foam was cut into 2×3 cm pieces with a thickness of 0.5 mm. It was then washed sequentially with acetone, ethanol, and deionized water, and dried. 50 mg of thiourea (CH4N2S) and 50 mg of ferrocene [Fe(C5H5)2] were placed in a ceramic boat, and the dried nickel foam was placed in the center of another ceramic boat. These two ceramic boats were then placed in a tube furnace, with the boat containing thiourea and ferrocene near the furnace inlet and the boat containing nickel foam near the furnace outlet. Argon gas was introduced into the tube furnace at a flow rate of 50 sccm, and the furnace was heated to 400°C and maintained for one hour to obtain Ni3S2 quantum wire-loaded single-atom material (denoted as Ni3S2@Fe-SACs). A schematic diagram of the preparation process is shown below. Figure 1 As shown.

[0042] Example 2

[0043] This embodiment provides a method for preparing Ni3S2 quantum wire-supported single-atom materials, including the following steps:

[0044] First, cut the nickel foam into 2×3 cm pieces, then wash it sequentially with acetone, ethanol, and deionized water, and then dry it. 50 mg of thiourea (CH4N2S) and 50 mg of ferrocene [Fe(C5H5)2] are placed in a ceramic boat, and the dried nickel foam is placed in the center of another ceramic boat. These two ceramic boats are then placed in a tube furnace, with the boat containing thiourea and ferrocene near the furnace inlet and the boat containing the nickel foam near the furnace outlet. Argon gas is introduced into the tube furnace at a flow rate of 50 sccm, and the furnace is heated to 500°C and maintained for one hour to obtain Ni3S2 quantum wire-loaded single-atom material.

[0045] Example 3

[0046] This embodiment provides a method for preparing Ni3S2 quantum wire-loaded single-atom material, comprising the following steps: First, cut nickel foam into 2×3 cm pieces with a thickness of 0.5 mm, then wash the nickel foam sequentially with acetone, ethanol, and deionized water, and then dry it; 50 mg of thiourea (CH4N2S) and 50 mg of ferrocene [Fe(C5H5)2] are loaded into a ceramic boat, and the dried nickel foam is placed in the center of another ceramic boat; then the two ceramic boats are placed in a tube furnace, wherein the ceramic boat containing thiourea and ferrocene is near the gas inlet of the tube furnace, and the ceramic boat containing nickel foam is near the gas outlet of the tube furnace; an argon gas flow is introduced into the tube furnace at a flow rate of 60 sccm, the tube furnace is heated to 400°C and maintained for one hour, thus obtaining the Ni3S2 quantum wire-loaded single-atom material.

[0047] Example 4

[0048] This embodiment provides a method for preparing Ni3S2 quantum wire-loaded single-atom material, comprising the following steps: First, cut nickel foam into 1×3 cm pieces with a thickness of 0.5 mm, then wash the nickel foam sequentially with acetone, ethanol, and deionized water, and then dry it; 50 mg of thiourea (CH4N2S) and 50 mg of ferrocene [Fe(C5H5)2] are loaded into a ceramic boat, and the dried nickel foam is placed in the center of another ceramic boat; then the two ceramic boats are placed in a tube furnace, wherein the ceramic boat containing thiourea and ferrocene is near the gas inlet of the tube furnace, and the ceramic boat containing nickel foam is near the gas outlet of the tube furnace; an argon gas flow is introduced into the tube furnace at a flow rate of 50 sccm, the tube furnace is heated to 400°C and maintained for one hour, thus obtaining the Ni3S2 quantum wire-loaded single-atom material.

[0049] Example 5

[0050] This embodiment provides a method for preparing Ni3S2 quantum wire-loaded single-atom material, comprising the following steps: First, cut nickel foam into 2×4 cm pieces with a thickness of 0.5 mm, then wash the nickel foam sequentially with acetone, ethanol, and deionized water, and then dry it; 50 mg of thiourea (CH4N2S) and 50 mg of ferrocene [Fe(C5H5)2] are loaded into a ceramic boat, and the dried nickel foam is placed in the center of another ceramic boat; then the two ceramic boats are placed in a tube furnace, wherein the ceramic boat containing thiourea and ferrocene is near the gas inlet of the tube furnace, and the ceramic boat containing nickel foam is near the gas outlet of the tube furnace; an argon gas flow is introduced into the tube furnace at a flow rate of 50 sccm, the tube furnace is heated to 400°C and maintained for one hour, thereby obtaining the Ni3S2 quantum wire-loaded single-atom material.

[0051] Example 6

[0052] This embodiment provides a method for preparing Ni3S2 quantum wire-loaded single-atom material, comprising the following steps: First, cut nickel foam into 2×3 cm pieces with a thickness of 0.5 mm, then wash the nickel foam sequentially with acetone, ethanol, and deionized water, and then dry it; 40 mg of thiourea (CH4N2S) and 50 mg of ferrocene [Fe(C5H5)2] are loaded into a ceramic boat, and the dried nickel foam is placed in the center of another ceramic boat; then the two ceramic boats are placed in a tube furnace, wherein the ceramic boat containing thiourea and ferrocene is near the gas inlet of the tube furnace, and the ceramic boat containing nickel foam is near the gas outlet of the tube furnace; an argon gas flow is introduced into the tube furnace at a flow rate of 50 sccm, the tube furnace is heated to 400°C and maintained for one hour, thus obtaining the Ni3S2 quantum wire-loaded single-atom material.

[0053] Example 7

[0054] This embodiment provides a method for preparing Ni3S2 quantum wire-loaded single-atom material, comprising the following steps: First, cut nickel foam into 2×3 cm pieces with a thickness of 0.5 mm, then wash the nickel foam sequentially with acetone, ethanol, and deionized water, and then dry it; 50 mg of thiourea (CH4N2S) and 40 mg of ferrocene [Fe(C5H5)2] are loaded into a ceramic boat, and the dried nickel foam is placed in the center of another ceramic boat; then the two ceramic boats are placed in a tube furnace, wherein the ceramic boat containing thiourea and ferrocene is near the gas inlet of the tube furnace, and the ceramic boat containing nickel foam is near the gas outlet of the tube furnace; an argon gas flow is introduced into the tube furnace at a flow rate of 50 sccm, the tube furnace is heated to 400°C and maintained for one hour, thus obtaining the Ni3S2 quantum wire-loaded single-atom material.

[0055] Example 8

[0056] This embodiment provides a method for preparing Ni3S2 quantum wire-loaded single-atom material, comprising the following steps: First, cut nickel foam into 2×3 cm pieces with a thickness of 0.5 mm, then wash the nickel foam sequentially with acetone, ethanol, and deionized water, and then dry it; 50 mg of thiourea (CH4N2S) and 50 mg of ferrocene [Fe(C5H5)2] are loaded into a ceramic boat, and the dried nickel foam is placed in the center of another ceramic boat; then the two ceramic boats are placed in a tube furnace, wherein the ceramic boat containing thiourea and ferrocene is near the gas inlet of the tube furnace, and the ceramic boat containing nickel foam is near the gas outlet of the tube furnace; an argon gas flow is introduced into the tube furnace at a flow rate of 60 sccm, the tube furnace is heated to 400°C and maintained for one hour, thus obtaining the Ni3S2 quantum wire-loaded single-atom material.

[0057] Example 9

[0058] This embodiment provides a method for preparing Ni3S2 quantum wire-loaded single-atom material, comprising the following steps: First, cut nickel foam into 2×3 cm pieces with a thickness of 0.5 mm, then wash the nickel foam sequentially with acetone, ethanol, and deionized water, and then dry it; 50 mg of thiourea (CH4N2S) and 60 mg of ferrocene [Fe(C5H5)2] are loaded into a ceramic boat, and the dried nickel foam is placed in the center of another ceramic boat; then the two quartz boats are placed in a tube furnace, wherein the ceramic boat containing thiourea and ferrocene is closer to the gas inlet of the tube furnace, and the ceramic boat containing nickel foam is closer to the gas outlet of the tube furnace; an argon gas flow is introduced into the tube furnace at a flow rate of 40 sccm, the tube furnace is heated to 400°C and held for one hour, thus obtaining the Ni3S2 quantum wire-loaded single-atom material.

[0059] Comparative Example 1

[0060] This comparative example provides a method for preparing Ni3S2 material, which is basically the same as that in Example 1, except that only 100 mg of thiourea (CH4N2S) is added to the ceramic boat at one end near the gas inlet of the tubular furnace, and ferrocene is not added, to obtain Ni3S2 material, denoted as Ni3S2 / NF.

[0061] Comparative Example 2

[0062] This comparative example provides a method for preparing RuO2 material, comprising the following steps: First, cut nickel foam into 2×3 cm pieces with a thickness of 0.5 mm. Then, wash the nickel foam sequentially with acetone, ethanol, and deionized water, and then dry it. Next, dissolve 0.1 mg of commercially available RuO2 powder in 900 mL of ethanol (analytical grade), and then add 100 mL of 5 wt% Nafion solution and stir until homogeneous to prepare a noble metal solution. Use a microsyringe to uniformly coat the noble metal solution onto the surface of the nickel foam to form a thin film. Place it in an oven to dry, and obtain the RuO2 material, denoted as RuO2 / NF.

[0063] Comparative Example 3

[0064] This comparative example provides a method for preparing nickel foam material, including the following steps: first, cut the nickel foam into 2×3 cm pieces, then wash the nickel foam with acetone, ethanol and deionized water in sequence, and then dry it to obtain nickel foam material, denoted as NF.

[0065] Sample characterization

[0066] The Ni3S2@Fe-SACs from Example 1 were subjected to electron microscopy, and the results are as follows: Figure 2 As shown in A to C, Figure 2 A, Figure 2 B and Figure 2 C represents SEM images at different magnifications; Ni3S2@Fe-SACs were imaged using transmission electron microscopy, and the results are as follows: Figure 2 As shown in D to E, Figure 2 D and Figure 2 E represents TEM images at different magnifications; compositional analysis of Ni3S2@Fe-SACs was performed using energy-dispersive X-ray spectroscopy, and the results are as follows: Figure 2 As shown in F. From Figure 2 As shown in A through E, a vertical array of nanowires is uniformly and densely distributed on the nickel foam substrate. The nanowires exhibit a tapered structure along the axial direction. These nanowires have a relatively uniform diameter of approximately 0.42 nm. Figure 2F indicates the successful synthesis of Ni3S2@Fe-SACs, with Ni, S, C, N, and Fe elements uniformly distributed on the Ni3S2@Fe-SACs material.

[0067] High-resolution TEM (HRTEM) was used to detect the single crystal characteristics of Ni3S2@Fe-SACs, and the results are as follows: Figure 3 As shown, a carbon shell of approximately 1.5 nm can be observed, and the lattice fringe spacing of the (110) plane of Ni3S2@Fe-SACs is 0.285 nm. Furthermore, Figure 3 The presence of numerous adjacent, isolated bright spots (marked with yellow circles) indicates the presence of atomically dispersed iron in the material, signifying the achievement of single-atom loading. This demonstrates the successful preparation of Ni3S2 quantum wire-loaded single-atom materials.

[0068] The phase structure and crystal structure of Ni3S2@Fe-SACs material were tested using X-ray diffraction (XRD), and the results are as follows: Figure 4 As shown, apart from the diffraction peaks of the nickel foam substrate, all others are considered to be orthorhombic Ni3S2 (JCPDS 44-1418), and no other impurities were detected.

[0069] High-resolution XPS spectra of Ni3S2@Fe-SACs at Ni 2p, Fe 2p, O 1s, N 1s, C 1s, and S 2p were analyzed, and the results are as follows: Figure 5 As shown, Figure 5 A through F correspond to Ni 2p, Fe 2p, O 1s, N 1s, C 1s, and S 2p, respectively. For the Ni 2p spectrum, there are typical Ni 2p doublets at binding energies ≈873 and ≈854, representing Ni 2p... 3 / 2 and Ni 2p 1 / 2 The satellite peaks corresponding to the two spin orbitals; in the S2p spectrum, the broad peak at approximately 163 eV can be decomposed into two peaks at 162.8 and 161.7 eV, respectively, which correspond to the S2p peaks. 1 / 2 and S2p 3 / 2 Very consistent, revealing S 2- The presence of ; according to the C1s spectrum, CC or C=C, CN, C=O bonds can be detected; in the N1s spectrum, it can be decomposed into a peak associated with pyrroline-N (398.8 eV) and two peaks associated with graphene-N (399.9 eV and 398.0 eV).

[0070] The above characterizations all demonstrate the successful synthesis of Ni3S2@Fe-SACs.

[0071] Performance testing

[0072] Electrochemical performance testing employed a three-electrode system, including a reference electrode, a working electrode, and a counter electrode. Ni3S2@Fe-SACs were used as the working electrode, and all electrochemical performance tests were conducted in a 1.0 M KOH electrolyte. Carbon rods and Hg / HgO electrodes served as the counter and reference electrodes, respectively, in the electrocatalysis. The Nernst equation was used to correct for the potential. Linear voltammetry (LSV), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and constant voltage chronoamperometry were used to investigate the electrochemical performance of Ni3S2@Fe-SACs in Example 1, Ni3S2 / NF in Comparative Example 1, RuO2 / NF in Comparative Example 2, and nickel foam (NF) in Comparative Example 3.

[0073] Figure 6 A is the OER polarization curve after iR correction, from... Figure 6 As shown in section A, the overpotential of RuO2 / NF is 269 mV, which is similar to that of Ni3S2 / NF. The overpotential of NF is 293 mV, while the overpotential of Ni3S2@Fe-SACs is only 227 mV, which is lower than the 265 mV of Ni3S2 / NF. This demonstrates that using ferrocene as a raw material to prepare Ni3S2 quantum wire-loaded single-atom materials can significantly improve the OER performance of the materials. The above indicates that the Ni3S2 quantum wire-loaded single-atom materials of the present invention have good OER performance.

[0074] Figure 6 B is the Tafel slope plot, from Figure 6 As shown in section B, the Tafel slopes of RuO2 / NF and NF are 280 mV / dec and 302 mV / dec, respectively, while the Tafel slope of Ni3S2 / NF is 94 mV / dec. Ni3S2 / NF has an overpotential very close to that of RuO2 / NF, but RuO2 / NF differs greatly in terms of electrocatalytic oxygen evolution kinetics. Furthermore, the Tafel slope of Ni3S2@Fe-SACs is 78 mV / dec, indicating that using ferrocene as a raw material can reduce the Tafel slope of single-atom materials supported on Ni3S2 quantum wires, thereby improving the electrocatalytic oxygen evolution ability of the catalyst.

[0075] The electrochemical active area is directly proportional to the double-layer capacitance, as shown by the CV curves at different scan rates. Figure 7 , Figure 7 The test samples A through D are Ni3S2@Fe-SACs and Ni3S2 / NF, respectively. 、 Using RuO2 / NF and NF, the double-layer capacitance of Ni3S2@Fe-SACs was calculated to be 80.0 mF / cm. 2 ( Figure 8 ,in, Figure 8 A represents the double-layer capacitance Cdl diagram. Figure 8 B represents the Nyquist plots at different overpotentials. The ratios of Ni3S2 / NF, RuO2 / NF, and NF are all approximately 58.0 mF / cm. 2 This indicates that the Ni3S2 quantum wire-supported single-atom material of the present invention has a larger electrochemical active area.

[0076] Stability is a crucial indicator in catalyst performance evaluation. In water electrolysis, stability can lead to cost savings in production. The stability of OER catalysts can be measured by determining the current density versus time, resulting in an OER time-measurement curve. Figure 9 As shown, at a constant current density of 10 mA / cm² -2 The Ni3S2@Fe-SACs catalyst maintained its current density for 12 hours without a significant decrease, indicating good stability as a catalyst. In contrast, the current densities of the other three materials all decreased significantly. This demonstrates the excellent stability of the Ni3S2 quantum wire-supported single-atom material of this invention.

[0077] The sample characterization and performance test results of the Ni3S2 quantum wire-loaded single-atom materials in Examples 2-9 are similar to those in Example 1.

[0078] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing Ni3S2 quantum wire-supported single-atom material, characterized in that, Includes the following steps: Thiourea and ferrocene are placed upstream of the gas flow, and nickel foam is placed downstream of the gas flow. The reaction is carried out at 400~500 °C for 1~1.5 hours to obtain the Ni3S2 quantum wire-supported single-atom material. The mass ratio of thiourea to ferrocene is 1:(0.8~1.5); The airflow is an inert gas flow; The airflow velocity is 40~60 sccm; The mass-to-volume ratio of thiourea to nickel foam is 1 mg: 0.003 cm³. 3 1mg: 0.006cm 3 1mg: 0.0075cm 3 Or 1mg: 0.008cm 3 ; The single atom in the Ni3S2 quantum wire-loaded single-atom material is an iron atom.

2. The preparation method according to claim 1, characterized in that, Placing the nickel foam downstream of the airflow also includes steps of cleaning and drying the nickel foam.

3. The preparation method according to claim 1, characterized in that, The reaction is carried out in a tube furnace.

4. A Ni3S2 quantum wire-supported single-atom material, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 3.

5. The application of the Ni3S2 quantum wire-supported single-atom material as a catalyst in water electrolysis for hydrogen production as described in claim 4.

6. The application according to claim 5, characterized in that, The catalyst is used to catalyze the electrochemical oxygen evolution reaction.